Clinical Effectiveness of Vestibular Shields in Orthodontic Treatment: A Scoping Review - Chaypat Simsuchin; Yong Chen; Sreekanth Kumar Mallineni (MDPI AG, 2022)
This systematic literature search was performed to determine the clinical effectiveness of vestibular shields (VSs) in children undergoing orthodontic treatment. A comprehensive electronic search was performed in May 2022 using three databases (Medline via PubMed, the Cochrane Central Register of Controlled Trials, and Ovid). The initial screening of articles was based on titles and abstracts. Studies meeting the inclusion criteria were retrieved for the final quality assessment and the methodological qualities were assessed according to the Newcastle-Ottawa Scale and Cochrane risk of bias. The initial search identified 262 publications, of which 15 studies were potentially eligible, with excellent intra-examiner reliability (K = 0.88). A total of five studies were selected for the final analysis, including one randomized controlled trial, three clinical trials, and one cohort study. VS may have potential impacts on orthodontic treatment, lips and dental arches, but further high-quality studies are warranted